Prevalence of Ciprofloxacin Resistance Among Gram-Negative Bacilli at a Specialist Hospital in Saudi Arabia (Bangladesh Journal of Medical Science, 2012)
Background: Resistance to antimicrobials of different structural classes including fluoroquinolones has arisen in a multitude of bacterial species both in the community and the hospitals. This may complicate the therapeutic management of infections. Decreased susceptibility to fluoroquinolones arises mainly by singlestep mutations in the gyrA and parC genes, which encode the fluoroquinolones targets, the topoisomerase enzymes, conferring cross resistance to all fluoroquinolones. Accumulation of multiple mutations in several genes confers increasing level of resistance associated with clinical failure. However, even low level resistance can generate therapeutic failure. In 1998, some mobile elements with a potential for the horizontal transfer of the quinolone resistance genes were described. The loci which are responsible for this plasmid-mediated quinolone resistance, which have been designated as qnrA, qnrB and qnrS, have been identified in the Enterobacteriaceae species. Aim: To evaluate the susceptibility pattern of the isolates to various antibiotics and to know the prevalence rate of ciprofloxacin resistance in our hospital. Materials & Methods: A total of 916 gram-negative bacilli (GNB) were isolated from different clinical specimens over a period of nine months, were subjected to antibiotic susceptibility testing. Isolates with resistance or with a decreased susceptibility to ciprofloxacin (£20 mm) were then screened for their minimum inhibitory concentration(MIC) by using the E-test. Results: Out of 916 GNB, 321 (35%) isolates were resistant to ciprofloxacin. The MIC of these isolates ranged from 4 to >32?g/ml.Conclusion: The resistance rate to ciprofloxacin was 35% in our study. Most of the ciprofloxacin resistant isolates were from urinary tract infections (UTI). The ciprofloxacin resistance was also closely associated with multi-drug resistance, thus limiting the treatment options. Ciprofloxacin resistance can be used as a general surrogate marker of multidrug resistance, thus limiting the already restricted treatment options. The considerably high MIC values for ciprofloxacin in this study reflected the extent of the treatment problems for these resistant isolates and a need for the continuous evaluation of the commonly used antibiotics. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12604 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12